2018
DOI: 10.1093/cid/ciy981
|View full text |Cite
|
Sign up to set email alerts
|

Noninfectious Comorbidity in the African Cohort Study

Abstract: Background Noninfectious comorbid diseases (NCDs) contribute to morbidity and mortality in human immunodeficiency virus (HIV)–infected populations in resource-rich countries. With antiretroviral therapy (ART) scale-up in Africa, understanding burden NCD informs public health strategy. Methods At enrollment, participants at 11 HIV clinics in Kenya, Uganda, Tanzania, and Nigeria underwent medical history, physical, laboratory, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 37 publications
(17 reference statements)
0
46
0
Order By: Relevance
“…The prevalence of hypertension has increased in Africa in recent decades, contrary to the decreasing trend in developed nations [16]. Amongst PLWH in sub‐Saharan Africa, the prevalence of hypertension has been reported to be between 13% and 15% [8,13]. The high prevalence of hypertension in our study cohort is particularly concerning given the strong association with a lower eGFR at baseline and 6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of hypertension has increased in Africa in recent decades, contrary to the decreasing trend in developed nations [16]. Amongst PLWH in sub‐Saharan Africa, the prevalence of hypertension has been reported to be between 13% and 15% [8,13]. The high prevalence of hypertension in our study cohort is particularly concerning given the strong association with a lower eGFR at baseline and 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…While complications of advanced HIV infection, such as opportunistic infections and cancer, are undoubtedly associated with malnutrition and low BMI, it has been suggested that excess body mass exerts an independent protective effect against HIV disease progression [7]. The interaction of BMI with HIV-specific outcomes in Sub-Saharan Africa is not well described and the wide variation in food security and obesity rates across the region makes local data essential for public health decision making [8][9][10][11]. Here, we report the prevalence of overweight and obesity and its association with NICMs, particularly hypertension and CKD, in a cohort of treatment-na€ ıve PLWH commencing ART at the Newlands Clinic in Harare, Zimbabwe.…”
Section: Introductionmentioning
confidence: 99%
“…These analyses used data from the African Cohort Study (AFRICOS), a longitudinal cohort enrolling adults engaged in care at 12 sites in Uganda, Kenya, Tanzania and Nigeria supported by the President's Emergency Plan for AIDS Relief (PEPFAR). AFRICOS participants provided a medical history, completed a physical examination and underwent laboratory assessments every six months as described previously . HIV diagnosis dates, ART start dates and CD4 nadir were obtained from medical record review.…”
Section: Methodsmentioning
confidence: 99%
“…36 African Cohort Study findings suggest that PLHIV on ART had an increased risk of noncommunicable diseases compared with those not on ART. 37 In addition, the AFRICOS is being used to monitor the transition to dolutegravir as first-line treatment, providing real-time data to inform program improvement. Preliminary data show that participants prescribed tenofovir/ lamivudine/dolutegravir (TLD) developed a higher BMI than those on other ART regimens (unpublished).…”
Section: Rv516mentioning
confidence: 99%
“…Comprehensive care will need to address noncommunicable diseases in PLHIV as they survive to older ages. 37 The cohort has also identified mental health as a driver of HIV outcomes, for example, describing depression as a predictor of HIV viral load. 38 Leveraging PEPFAR sites for impact.…”
Section: Rv516mentioning
confidence: 99%